FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MELAKSANAKAN KEWAJIBAN PERPAJAKAN OLEH WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS UMKM DI KOTA PEKANBARU (Studi Empiris Pada KPP Pratama Pekanbaru Tampan) - Yunita, Ria; Ratnawati, Vince; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine wheter there a relationship among taxplayer awareness, knowlage, understanding and modernizations of the tax administration system on the willingness to implement tax obligations. The data was obtained from individual who works on Small and Medium Enterprices (SMEs) in Pekanbaru consisting of District Tampan, District Payung Sekaki, District Marpoyan Damai, District Rumbai and District Rumbai Coastal that the total number of units of micro, small and medium entreprises is 8832 units . The number of questionnaires distributed 100 pieces of questionnaires. But eventually that can be used for further analysis of questionnaires is 77 questionnaires. Use the method of sampling is convenience sampling This study used Partial Least (PLS) in test validity. The results of this study were obtained awareness t hitung > t tabel (6.49 > 1.993), knowledge t hitung > t tabel (6.68 > 1.993), understanding t hitung < t table (0.18 < 1.993), and the modernization of the tax administration system t hitung > ttabel ( 3.01 > 1.993). The result indicate that awareness, knowlage and the modernization of the tax administration system has positive on the implement tax obligations. However, understanding negatively affect the willingness to implement tax obligations.Keywords : Awareness, Knowledge, Understanding, Modernization and Willingness